Low temperature synthesis of MgTa2O6 powders - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare MgTa2O6 (MT) ceramics. Freshly prepared niobium hydroxide gel is mixed with magnesium hydroxide thoroughly and allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 550 degrees C to form crystalline MgTa2O6. This is the lowest temperature so far reported for the formation of MgTa2O6. For comparison, MT powders were also prepared by the traditional solid state method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 40 nm for the low temperature calcined powders. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; magnesium tantalate; Oxides; X-ray diffraction

Preparation of fine MgTa2O6 and Mg4Ta2O9 powders by chemical methods - Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Two different chemical methods are applied to prepare MgTa2O6 (MT2) and Mg4Ta2O9 (M4T2) powders. A gel was formed when a aqueous solution of Mg(NO3)(2), TAF(5) and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 750 degrees C produced the fine crystallites of ternary oxide, M4T2. A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase MT2. Ammonium hydroxide was used to precipitate Mg2+ and Ta5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees produces MT2 powders. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; powders-chemical preparation; X-ray methods

Preparation of nanocrystalline LiNbO3 by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A gel was formed when an aqueous solution of Li(NO3) NbF5 and citric acid in stoichiometric ratio is heated in a water bath at 100 degrees C. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, LiNbO3 (LN). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; lithium niobate; X-ray diffraction

Preparation of ultrafine LiTaO3 powders by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of Li(NO3), TaF5 and citric acid in stoichiometric ratio was heated in a water bath. This gel on decomposition at 700 degrees C produced fine crystallites of ternary oxide, LiTaO3 (LT). The phase contents and lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

TiO2 ceramic varistor modified with tantalum and barium - Gaikwad, A. B.; Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
The non-linear current (I)-voltage (V) characteristics of titanium dioxide doped with small quantities of tantalum and barium (99.9 TiO2 + 0.1 Ta and 99.4 TiO2 + 0.1 Ta + 0.5 Ba, all are in at.%) were investigated. These samples have the non-linear coefficient (alpha) values of (20-30) with high breakdown voltages (E-B similar to 400-700 V mm(-1)). The pentavalent tantalum acts as donor and increases the electronic conductivity. The higher electrical conductivity and decrease in the breakdown field strength with barium addition is attributed to higher density. The acceptor like surface states formed by barium ions segregate to grain boundaries due size misfit to thereby modifying the electrical barrier characteristics of grain boundaries. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Oxides; TiO2; varistor; X-ray diffraction

Coprecipitation technique to prepare LiTaO3 powders - Navale, SC; Gaikwad, A. B.; Ravi, V (Materials Letters, 2006)
A simple coprecipitation technique had been successfully applied for the preparation of pure ultrafine single phase LiTaO3 (LT). An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Li+ and Ta5+ cations as carbonate and hydroxide respectively. This precursor oil heating at 750 degrees C produces LT powders. For comparison, LT powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction